P136 OCCASIONAL DIAGNOSIS OF B–CELL LYMPHOMA DURING A SCREENING EXAMINATION FOR HYPERTENSIVE CARDIOMYOPATHY: A CASE REPORT. (18th May 2022) - Deserio, M; Sanguettoli, F; Pavasini, R; Passarini, G; Tonet, E; Guardigli, G; Campo, G
Abstract: Background: Echocardiography is fundamental in identifying early "red flags" of infiltrative cardiomyopathy in patients with monoclonal gammopathy and left ventricular hypertrophy. Nonetheless, definite diagnosis of cardiac amyloidosis requires multimodality imaging such as cardiac magnetic resonance, whole body bone scintigraphy and eventual biopsy in order to determine the disease phenotype. Case Report: A 79 year–old male affected by Monoclonal Gammopathy of Undetermined Significance (IgM kappa) underwent a routinary echocardiography examination for arterial hypertension. The exam showed septal hypertrophy (diastolic septum width 13 mm) and right ventricular hypertrothy, E/e'>14 and valvular thickening. Based on these red flags in MGUS, in order to exclude cardiac amyloidosis, a whole body bone scintigraphy was performed: the exam was negative for myocardial uptake. Laboratory tests showed increased free kappa light chain component (61, 9 mg/L (r.v. 3.3–19.4), with lambda resulting 5, 46 mg/l (r.v. 5.71–26.3), a k/l ratio of 11.34 (r.v. 0.26–1.65) and absence of Bence Jones proteinuria Subsequent cardiac MRI was performed and two restricted areas of subendocardial LGE were documented on the lateral and apical left ventricular wall without corresponding regional motion abnormalities: the findings were consistent with pathologic accumulation. In relation to the subendocardial localization of the abnormalities, obstructive coronaropathy was excluded by performing a coronary computed tomography angiography (CCTA). Abdominal Fat Biopsy was negative for amyloid protein. Osteo–medular biopsy displayed an IgM kappa lymphoplasmacytic lymphoma. Cardiological findings were, therefore, interpreted as markers of initial myocardial infiltration from a plasmacytoma. Afterwards, patient's therapy and clinical follow up were managed by the Hematology care. Discussion: Myocardial infiltration from plasmacytoma is very rare in comparison to Multiple myeloma and it features a more focal, less homogeneous pattern. In this case, recognizing red flags on echocardiography allowed an early diagnosis.